Peningkatan Media Pembelajaran Interaktif Berbasis Adobe Flash CS6 Untuk Meningkatkan Hasil Belajar Siswa Kelas X pada Mata Pelajaran Komputer Grafis di SMK Plus Pertiwi Sukamulya - Jeni, Jeni; Lutfi , Ahmad Fajri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to improve the learning outcomes of Grade X students in the Graphic Design subject at SMK Plus Pertiwi Sukamulya through the implementation of interactive learning media based on Adobe Flash CS6. The research method used is a quantitative approach with a one-group pretest-posttest design. The research sample consists of 20 Grade X students majoring in Visual Communication Design (DKV), who will be given an initial test (pretest) to measure their baseline abilities in the Graphic Design subject. Subsequently, the students will undergo the learning process using interactive media based on Adobe Flash CS6. After the learning process, the students will be given a final test (posttest) to measure the improvement in their learning outcomes. The data from the pretest and posttest will be analyzed using descriptive and inferential statistics with the assistance of SPSS and Microsoft Excel. The pretest results showed the highest score of 87 and the lowest score of 40, with an average score of 64.05. Following the implementation of the interactive learning media based on Adobe Flash CS6, the posttest results indicated the highest score of 93 and the lowest score of 53, with an average score of 75.70, reflecting an improvement of 11.65. Therefore, it can be concluded that the posttest results showed a higher average score compared to the pretest, and there is a significant difference between the pretest and posttest scores